Max a novel - Fast, Howard 1914-2003 (Houghton Mifflin, 1982)
The story of an enterprising young man who works his way from humble beginnings on New York's Lower East Side to success in Hollywood fledgling film industry.
Keywords: Motion picture industry -- Fiction; Fiktionale Darstellung